Pelatihan Pencegahan Faktor Risiko Malaria pada Siswa Sekolah di SMP Negeri 1 Manganitu - Dismo Katiandagho; Jasman; Suwarja; Joy V.I. Sambuaga (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Malaria infection is still a clinical problem in developing countries, especially countries with tropical climates, including Indonesia. The aim of this activity is to increase students' knowledge by providing training on preventing malaria risk factors for school students at SMP Negeri 1 Manganitu. The method used in this activity is providing training on preventing malaria risk factors to students at SMP Negeri 1 Managanitu, which aims to increase students' knowledge and train school children to become malaria interpreters from an early age, and introduce risk factors that cause malaria for the community in general and school children in specifically. As a result of the training, all students at SMP Negeri 1 Manganitu already know the type of plasmodium that causes malaria and the risk factors that cause malaria, and all students know the types of plasmodium that cause malaria. breading place Anopheles mosquito larvae in the school environment. It is recommended that the school, both teachers and students of SMP Negeri 1 Manganitu, always clean breading place Anopheles mosquito larvae in the school environment.